2021
DOI: 10.1007/s11367-021-01971-5
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and social life cycle assessment of growing media for urban rooftop farming

Abstract: Purpose New environmental strategies are emerging for cities to become more self-sufficient, such as hydroponic crop production. The implementation of such systems requires materials that usually originate in countries with low labour costs and other legal regulations. To what extent could these strategies be shifting problems across the globe? To answer this question, we performed a comprehensive environmental and social assessment of the various extended soilless systems used to grow vegetables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 57 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…Production costs have increased while the price at origin of fruits and vegetables has remained constant. In addition, there has been competition with developing countries that produce their goods at lower costs mainly because they spend less on labor [2,4].…”
Section: Introductionmentioning
confidence: 99%
“…Production costs have increased while the price at origin of fruits and vegetables has remained constant. In addition, there has been competition with developing countries that produce their goods at lower costs mainly because they spend less on labor [2,4].…”
Section: Introductionmentioning
confidence: 99%
“…For IVFs, the choice of substrate can also have a significant influence on the environmental performance of an IVF. Previous research has shown that substrates such as perlite and peat may have large environmental impacts, while lower environmental impacts are found for by-products such as coir (Martin et al, , 2022Quantis, 2012;Toboso-Chavero et al, 2021;Vinci and Rapa, 2019). The use of peat also continues to be controversial (Chapman et al, 2003;Hojlund, 2008;Salomaa et al, 2018).…”
Section: Substratesmentioning
confidence: 99%
“…Metropolises prioritized ecological environment benefits, MSCs emphasized social and private economic benefits, and FMCs placed a greater emphasis on private economic benefits [49]. Further research by Toboso-Chavero et al [50] evaluated various growing media (perlite, peat, and coir) for urban rooftop farming using the social LCA method. The research concluded that peat emerged as the most socially amenable growing medium, showcasing superior indicators in impact categories such as community infrastructure, human rights, and labor rights and decent work when juxtaposed with other alternatives [50].…”
Section: Life Cycle Social Performancementioning
confidence: 99%
“…Literature analysis revealed that of the 260 studies on GRs, only 3 [48,50,69] have addressed the social performance of GRs, with just 1 [50] examining social benefits from a life cycle perspective. This highlights the need for the further exploration of S-LCA in GI.…”
Section: Social Life Cycle Assessmentmentioning
confidence: 99%